Phase II/III Study of Lisdexamfetamine Dimesylate in Japanese Pediatric Patients with Attention-Deficit/Hyperactivity Disorder - Ichikawa, Hironobu (J Child Adolesc Psychopharmacol, 2020)
Objective: To further define the efficacy and safety profiles of lisdexamfetamine dimesylate (LDX) in Japanese pediatric patients with attention-deficit/hyperactivity disorder (ADHD). Methods: This was a multicenter, randomized, double-blind, placebo-controlled study of LDX 30, 50, or 70 mg/day for 4 weeks in 76 patients 6–17 years of age with ADHD in Japan. The primary efficacy endpoint was the change in the ADHD Rating Scale-IV (ADHD-RS-IV) total score from baseline to 4 weeks. Secondary efficacy endpoints were: Conners' Third Edition (Japanese version) Parent Rating Scale (Conners 3), Clinical Global Impression-Improvement (CGI-I) scale, and Parent Global Assessment (PGA) scale. Results: Change in the ADHD-RS-IV total score from baseline to 4 weeks was significantly greater (p < 0.0001) in all LDX dosage groups versus placebo (30 mg, −16.38; 50 mg, −18.10; 70 mg, −16.47; placebo, −2.78). At all time points, improvements (decreases) in the ADHD-RS-IV total score were significantly greater in all LDX groups versus placebo. At weeks 3 and 4, improvements from baseline in Conners 3 inattention plus hyperactivity/impulsivity subscale scores were significantly greater (p ≤ 0.0082) for all LDX dosages versus placebo. At week 4, the proportion of LDX-treated patients “much improved” or “very much improved” was 61%–71% on the CGI-I scale (p ≤ 0.0019) and 56%–65% on the PGA scale (p ≤ 0.0170). LDX was generally well tolerated. The most frequent treatment-emergent adverse events (AEs) were decreased appetite, headache, and initial insomnia. No severe/serious AEs occurred, and no AEs specific to Japanese patients were evident. Conclusions: The superiority of LDX 30, 50, and 70 mg/day over placebo was confirmed in Japanese pediatric patients with ADHD, and no major safety or tolerability concerns were identified.